18F-FDG PET/CT imaging findings of multiple solitary fibrous tumor: A case report. Issue 32 (August 2019) - Liu, Xiaofei; Zhu, Wenhua; Zhou, Xiaohong; Yao, Hao; Su, Jiagui; Ouyang, Xiaohui; He, Baoming
Abstract: Rationale: Solitary fibrous tumor(SFT) is a rare and distinct clinical entity. There are few descriptions in the literature regarding the PET manifestations of SFTs. Herein, we report a case of multiple malignant SFT with PET/CT imaging findings and PET/Contrast Enhanced CT image findings. Patient concerns: A 30-year-old woman presented with a history of a mass in neck increased gradually over 6 months without jaundice or other symptoms of obstruction.Serum laboratory results and tumor markers (AFP, CEA, CA199, CA724, CA153 and CA125)were normal. The whole body PET/CT scan showed lightly or mildly hypermetabolic and inhomogeneous metabolic which was different from other reports, and it was the first report of 18F-FDG-PET/CT findings of multiple malignant SFTs, which were confirmed by positive immunohistochemical staining for CD2-40, CD99, SMA and negative immunohistochemical staining for S100 and CD34. Diagnoses: She was diagnosed with multiple malignant solitary fibrous tumors which was confirmed by pathological results and 18F-FDG-PET/CT findings. Interventions: The patient didn't receive any treatment because she was not suitable for surgery and refused any other therapy. Outcomes: The patient has been followed up for one year, and she was still alive. Lessons: SFTs should be detected early and treated early.It was of high value in the diagnosis and differential diagnosis of SFTs by PET/CT imaging findings, which can not only identify the benign and malignant lesions, but also identify the lesion involved range.